USER SATISFACTION ANALYSIS OF SITANOS APPLICATION AT CLASS I NON-TPI TANGERANG IMMIGRATION OFFICE WITH END-USER COMPUTING SATISFACTION (EUCS) METHOD - G.A Nursanto; I.A Prabadhi; A.R Pratama (Polteknik Imigrasi, 2022)
The Covid-19 pandemic has hampered community activities, including in terms of public services, including in the field of Immigration. Tangerang Immigration Office made a breakthrough during the Covid-19 pandemic by creating the Tangerang Online Service Immigration Application (SITANOS), a website-based application. The SITANOS application provides various immigration services. In running an application, it is necessary to know how satisfied the application users are by looking at the level of user satisfaction. This study aims to measure user satisfaction with the SITANOS application. The method used is End User Computing Satisfaction (EUCS). The data processing results shown in the T-Statistics test found in the five hypotheses that ned, two variables were accepted: Accuracy and Ease of Use. At the same time, the three variables rejected variables, Format, and Timeliness. These results indicate that, in practice, the level of accuracy and ease of use in the application is good. However, in terms of the completeness of the content (Content), the display provided (Format), and the timeliness of presenting information (Timeliness) must be further improved and redeveloped so that people feel satisfied with using the SITANOS application.